Collider and astrophysical signatures of light scalars with enhanced τ couplings - Jorge Alda; Gabriele Levati; Paride Paradisi; Stefano Rigolin; Nudžeim Selimović (Journal of High Energy Physics)
Abstract Beyond Standard Model scenarios addressing the flavor puzzle and the hierarchy problem generally predict dominant new physics couplings with fermions of the third generation. In this Letter, we explore the collider and astrophysical signatures of new light scalar and pseudoscalar particles dominantly coupled to the τ-lepton. The best experimental prospects are expected at Belle II through the e + e − → τ + τ − γγ, τ + τ − γ, 3γ, mono–γ processes, and the τ anomalous magnetic moment. The correlated effects in these searches can unambiguously point toward the underlying new physics dynamics. Moreover, we study astrophysics bounds — especially from core-collapse supernovae and neutron star mergers — finding them particularly effective and complementary to collider bounds. We carry out this program in the well-motivated context of axion-like particles as well as generic CP-even and CP-odd particles, highlighting possible ways to discriminate among them.